Coagulopathy as a predictor of the effectiveness of tranexamic acid in severe blunt trauma: a multicenter retrospective study - Yuki Takahashi; Mineji Hayakawa; Yuki Itagaki; Kota Ono; Daisuke Kudo; Shigeki Kushimoto (Thrombosis Journal)
Abstract Background Tranexamic acid (TXA) reduces mortality in severe trauma cases. However, the relationships between TXA administration and coagulation/fibrinolysis abnormalities are unclear. We performed a retrospective observational study to investigate relationships between mortality and coagulation/fibrinolysis abnormalities of patients on arrival at the emergency department and whether TXA is more effective in patients with severe trauma who have coagulation/fibrinolysis abnormalities than in those who do not. Methods Data was collected from 15 tertiary emergency and critical care centers in Japan. Adult patients with blunt trauma and an Injury Severity Score of ≥ 16 were included in the study. Patients were categorized into two groups: the TXA group received TXA within 3 h of arrival, and the non-TXA group did not. Results Overall, 790 patients were included (TXA group, 276; non-TXA group, 514). In cubic spline curves for relationships between mortality and coagulation/fibrinolysis variables on arrival, odds for mortality increased and plateaued with a prothrombin time-international normalized ratio ≥ 1.2; the disseminated intravascular coagulation (DIC) score showed a marked odds increase when > 4 points. Odds increased and plateaued from an activated partial thromboplastin time (APTT) of ≥ 35 s and gradually increased as fibrinogen decreased from 250 mg/dL. Fibrinogen and fibrin degradation products (FDP) and D-dimer exhibited upward-sloping curves. In cubic spline curves for relationships between the effectiveness of TXA administration and coagulation/fibrinolysis variables on arrival, a favorable effect on mortality was observed with TXA administration when fibrinogen was ≤ 200 mg/dL or when the DIC score was ≥ 4 points; FDP, ≥ 50 µg/mL; D-dimer, ≥ 30 µg/mL; or APTT, ≥ 35 s. In each threshold subgroup, interactions between TXA administration and in-hospital mortality were observed. Conclusions TXA demonstrates increased effectiveness in patients with traumatic coagulation/fibrinolysis abnormalities.